Outlines of Political Thinking in Kant's Critical Philosophy - Ivanauskas, Lukas (Politologija, 2024)
Immanuel Kant’s critical philosophy revolutionised thinking and left unanswered the question of how politics as philosophy and science is possible. Hannah Arendt was right to associate politics with the reflective power of decision, but she left unanswered the questions of what conception of politics is implied by Kant’s critical system and what are the limits of political philosophy and political science. The paper argues that politics is an aesthetic idea and therefore has no objectively universal definition and remains necessarily open to interpretation by various epistemic and political communities. Aesthetic ideas also substantiate the possibility of political science as symbolic cognition and reformulate the challenge of political philosophy to confine politics solely within the judgment.
Keywords: Kant; political science; political philosophy; thinking; aesthetic ideas